2022
DOI: 10.1021/acs.est.2c02297
|View full text |Cite
|
Sign up to set email alerts
|

Boron Removal from Reverse Osmosis Permeate Using an Electrosorption Process: Feasibility, Kinetics, and Mechanism

Abstract: Boron is present in the form of boric acid (B­(OH)3 or H3BO3) in seawater, geothermal waters, and some industrial wastewaters but is toxic at elevated concentrations to both plants and humans. Effective removal of boron from solutions at circumneutral pH by existing technologies such as reverse osmosis is constrained by high energy consumption and low removal efficiency. In this work, we present an asymmetric, membrane-containing flow-by electrosorption system for boron removal. Upon charging, the catholyte pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…However, no apparent difference in pH variation was observed in the absence and presence of NO 3 – (SI Figure S5), suggesting the pH increase was mainly due to the occurrence of water electrolysis and/or oxygen reduction. This finding is also supported by our previous study, which also showed that water electrolysis is the major cause of pH increase at a cell voltage >2.3 V . The increase in pH changes the speciation of NH 4 + (p K a = 9.2) to NH 3, thereby facilitating stripping of NH 3 by the FGM-attached acid-receiving chamber.…”
Section: Resultsmentioning
confidence: 98%
“…However, no apparent difference in pH variation was observed in the absence and presence of NO 3 – (SI Figure S5), suggesting the pH increase was mainly due to the occurrence of water electrolysis and/or oxygen reduction. This finding is also supported by our previous study, which also showed that water electrolysis is the major cause of pH increase at a cell voltage >2.3 V . The increase in pH changes the speciation of NH 4 + (p K a = 9.2) to NH 3, thereby facilitating stripping of NH 3 by the FGM-attached acid-receiving chamber.…”
Section: Resultsmentioning
confidence: 98%
“…Another electrosorption configuration that has recently demonstrated boron removal capability resembles membranecapacitive deionization (MCDI). 23 However, unlike conventional MCDI, only an anion-exchange membrane is placed in front of the anode, while the cathode remains bare. Thus, when sufficiently high potentials are applied (i.e., >2.0 V used in the study), oxygen reduction and water splitting are induced at the cathode, in turn producing hydroxide ions which migrate to the flow channel.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another electrosorption configuration that has recently demonstrated boron removal capability resembles membrane-capacitive deionization (MCDI) . However, unlike conventional MCDI, only an anion-exchange membrane is placed in front of the anode, while the cathode remains bare.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Thus, it holds great promise to alleviate, or at least change the dynamics of, the worldwide water scarcity problem. 7,8 The desalination performance of a CDI system is intrinsically associated with the employed electrode materials, so researchers are dedicated to exploring novel electrode materials with a high desalination capacity to accelerate the industrial process of the technology. In response, by virtue of their multiple merits of metal-grade conductivity (6500 S cm −1 ), high volumetric capacitance (1500 F cm −3 ), and unique layered structure allowing rapid ion de-/intercalation, twodimensional transition metal carbides/nitrides (e.g., M n+1 X n , where M is the transition metal and X is carbon or nitrogen), commonly referred to as MXenes, may serve as one of the most promising faradic pseudocapacitance electrode materials and, correspondingly, have great prospects for use in CDI technology.…”
Section: ■ Introductionmentioning
confidence: 99%